FORMATION OF TURKOLOGY AS A LINGUISTIC SCIENCE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article deals with the emergence of Turkology as a separate scientific branch. Turkology originated as a complex of humanities and social sciences, studying languages, history, literature, oral folk art, material and spiritual culture of the Turkic-speaking peoples and currently has its significant place in the world system of science and education. The founders of the formation of Turkology as a complex humanitarian and social scientific direction are the great Altaist Turkologists. The article examines the scientific heritage of these scientists in the context of a particular Turkic language.
Keywords: Turkology, Turkic languages, Altasit-Turkologists, scientific heritage, grammar, phonetics, lexicography